Extended-reach WDM-PON based on CW supercontinuum light source for colorless FP-LD based OLT and RSOA-based ONUs - Lee, Ju Han; Lee, Kwanil; Lee, Sang Bae; Kim, Chul Han (ELSEVIER SCIENCE INC, 2009)
We investigate the benefits of using our proposed continuous-wave supercontinuum (CW SC) as a broadband wavelength-locking source for the implementation of extended-reach, colorless, wavelength division-multiplexed passive optical networks (WDM-PONs). More specifically, first, an extended reach WDM-PON architecture based on both the CW SC and our devised C-/L-band beam combiner is proposed, in which the optical line terminal (OLT) is based on Fabry-Perot laser diodes (FP-LDs), whereas the optical network units (ONUs) are reflective semiconductor optical amplifiers (RSOAs). Second, a theoretical investigation on the maximum reach achievable with the proposed architecture is carried out considering Rayleigh backscattering noise and injection power limits. Only upstream signal performance is compared for the following four cases: (1) superluminescent diode (SLD) broadband source and FP-LD ONU, (2) SLD and RSOA, (3) CW SC and FP-LD, and (4) CW SC and RSOA. The combination of a CW SC injection source and RSOA-based ONUs is found to allow for the longest distance coverage. Finally, the feasibility of the proposed architecture is experimentally analyzed over a 60-km transmission fiber at 622 Mbit/s. (C) 2009 Elsevier Inc. All rights reserved.